2022
DOI: 10.3389/fnins.2022.912798
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal explainable AI predicts upcoming speech behavior in adults who stutter

Abstract: A key goal of cognitive neuroscience is to better understand how dynamic brain activity relates to behavior. Such dynamics, in terms of spatial and temporal patterns of brain activity, are directly measured with neurophysiological methods such as EEG, but can also be indirectly expressed by the body. Autonomic nervous system activity is the best-known example, but, muscles in the eyes and face can also index brain activity. Mostly parallel lines of artificial intelligence research show that EEG and facial musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…In the medical domain, multimodal data are often complementary with each other, meaning that each type of data (e.g. images, sensor data, text report) can be used to extract unique latent representations to allow a better understanding of a pathology [160] 2021 Predictive Seizure Forecasting Private 3 Saeed et al [161] 2021 Multiple Multiple HHAR [144], MobiAct [147], MotionSense [149], UCI HAR [146], HAPT [162], Sleep-EDF [131], MIT Driver DB [163], WiFi CSI [164] 4 Spathis et al [165] 2021 Predictive (HR forecasting) Subject Health Private 5 Thiam et al [166] 2021 Generative Pain Classification BioVid heat pain [167], SenseEmotion [168] 6 Das et al [169] 2022 Predictive Stuttering prediction Private 7 Deldari et al [170] 2022 Contrastive (COCOA) Multiple UCI HAR [146], SLEEP-EDF, PAMAP2 [171], WE-SAD [87], Opportunity [172] 8 Lemkhenter et al [173] 2022 Predictive (PhaseSwap)…”
Section: Discussion and Open Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the medical domain, multimodal data are often complementary with each other, meaning that each type of data (e.g. images, sensor data, text report) can be used to extract unique latent representations to allow a better understanding of a pathology [160] 2021 Predictive Seizure Forecasting Private 3 Saeed et al [161] 2021 Multiple Multiple HHAR [144], MobiAct [147], MotionSense [149], UCI HAR [146], HAPT [162], Sleep-EDF [131], MIT Driver DB [163], WiFi CSI [164] 4 Spathis et al [165] 2021 Predictive (HR forecasting) Subject Health Private 5 Thiam et al [166] 2021 Generative Pain Classification BioVid heat pain [167], SenseEmotion [168] 6 Das et al [169] 2022 Predictive Stuttering prediction Private 7 Deldari et al [170] 2022 Contrastive (COCOA) Multiple UCI HAR [146], SLEEP-EDF, PAMAP2 [171], WE-SAD [87], Opportunity [172] 8 Lemkhenter et al [173] 2022 Predictive (PhaseSwap)…”
Section: Discussion and Open Challengesmentioning
confidence: 99%
“…The last two selected multimodal approaches combine biosignals with video recordings. Leveraging a combination of EEG and facial activity data extracted from video, Das et al [169] trained an explainable AI model to predict upcoming speech stuttering. Also, Martini et al [160] showed the potentiality of multimodal self-supervised learning by combining stereoencephalography (SEEG) and video data to forecast seizure events in drug resistant epileptic subjects.…”
Section: Multimodal Self-supervised Learning With Biosignalsmentioning
confidence: 99%
“…Leveraging a combination of EEG and facial activity data extracted from video, Das et al . [185] trained an explainable AI model to predict upcoming speech stuttering, while Martini et al . [178] showed the potentiality of multimodal selfsupervised learning by combining stereoencephalography (SEEG) and video data to forecast seizure events in drug resistant epileptic subjects.…”
Section: Multimodal Self-supervised Learning With Biosignalsmentioning
confidence: 99%
“…2.1.3 Dysfluent Speech Recognition. Technical work on improving speech assistants for PWS has focused on ASR models [8,23,31,35,50,51,61], stuttering detection [43], dysfluency detection or classification [22,40,42,48,56], clinical assessment [11], and dataset development [12,37,42,55]. Shonibare et al [61] and Mendelev et al [50] investigate training end-to-end RNN-T ASR models on speech from PWS.…”
Section: Overview Of Speech Recognition Systemsmentioning
confidence: 99%
“…Research on speech technology for PWS has largely focused on technical improvements to automatic speech recognition (ASR) models [31,35,50,51,61], dysfluency detection [22,40,42,48], and dataset development [12,37,42,55]. This body of work has largely lacked a human-centered approach to understanding the experiences that PWS have with speech recognition systems [17], which could in turn inform how to prioritize and advance technical improvements.…”
Section: Introductionmentioning
confidence: 99%